Retroperitoneoscopic Miniport Pyeloplasty in Children: A Single-Center Experience - Ozden, Ender; Bostanci, Yakup; Atac, Fatih; Genc, Gurkan; Yakupoglu, Yarkin Kamil; Sirtbas, Aykut; Sarikaya, Saban (Mary Ann Liebert Inc, 2012)
…